Effect of mixing proportion on the properties of seaweed modified sustainable concrete - Siddique, Md. Nurul Islam; Zularisam, A. W. (American Institute of Physics Inc., 2017)
Although the application of organic polymer has already been reported in the development of polymer modification process the use of carbohydrate polymer hasn’t been reported till date. The effect of mixing ratio of seaweed modified mortar on the properties of sustainable concrete was investigated. A number of mixing ratios of seaweed (gel) with cement, sand and water (such as 0.1; 0.6; 1.1; 6) was studied in this work. In addition, a range of mixing ratios of seaweed (powder) with cement, sand and water (such as 0.1; 0.3; 0.6; 1.1; 2.1, 5.1) was examined. The performance of the seaweed modified sustainable concrete was evaluated by compressive and splitting strength. Results revealed that seaweed modified concrete with mixing ratio (0.6) was optimum. This ratio produced significant compressive and splitting strength of 30 MPa and 5 MPa for 28 days, respectively.